2019
DOI: 10.1038/s41467-019-11891-6
|View full text |Cite
|
Sign up to set email alerts
|

Altered dendritic spine function and integration in a mouse model of fragile X syndrome

Abstract: Cellular and circuit hyperexcitability are core features of fragile X syndrome and related autism spectrum disorder models. However, the cellular and synaptic bases of this hyperexcitability have proved elusive. We report in a mouse model of fragile X syndrome, glutamate uncaging onto individual dendritic spines yields stronger single-spine excitation than wild-type, with more silent spines. Furthermore, fewer spines are required to trigger an action potential with near-simultaneous uncaging at multiple spines… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 55 publications
(79 reference statements)
2
40
0
1
Order By: Relevance
“…Reduced orientation tuning of the neurons in the visual cortex correlated with the decreased ability to resolve different orientations of sinusoidal grating stimuli in both mice and human individuals with FX (Goel et al, 2018 ). Furthermore, altered dendritic spine function and integration were found in layer 4 of the somatosensory cortex in FX mice (Booker et al, 2019 ). Structural and functional imaging studies of FX mice revealed local hyperconnectivity and long-range hypoconnectivity in V1 (Haberl et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Reduced orientation tuning of the neurons in the visual cortex correlated with the decreased ability to resolve different orientations of sinusoidal grating stimuli in both mice and human individuals with FX (Goel et al, 2018 ). Furthermore, altered dendritic spine function and integration were found in layer 4 of the somatosensory cortex in FX mice (Booker et al, 2019 ). Structural and functional imaging studies of FX mice revealed local hyperconnectivity and long-range hypoconnectivity in V1 (Haberl et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that the observed reduction in ADBE reflects a compensatory or homeostatic mechanism to counteract the increased excitability in FXS and Fmr1 KO models (Booker et al, 2019; Das Sharma et al, 2020; Zhang et al, 2014). BK channel openers decrease hyperexcitability in Fmr1 KO models both in vitro and in vivo by increasing hyperpolarization, resulting in decreased calcium influx in nerve terminals.…”
Section: Resultsmentioning
confidence: 99%
“…A homeostatic reduction in ADBE in response to increased hyperexcitability would not be a homogenous adaptation across the brain, since neurons that display high firing rates would be disproportionately impacted. Therefore, even if reduced ADBE is not a causal mechanism in FXS, it may still be a valuable therapeutic intervention point to correct hyperexcitability in specific circuits (Booker et al, 2019; Das Sharma et al, 2020). Future studies are now required to determine whether modulation of ADBE can sculpt circuit activity in FXS (and other autism models that display hyperexcitability - such as SynGAP haploinsufficiency disorder (Gamache et al, 2020)).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that MIS generation is an efficient mechanism to increase connectivity and/or strengthen connections on existing synapses during learning. Furthermore, in neurological disorders characterized by increased cortical connectivity and disrupted network function such as Fragile X syndrome (Bureau et al, 2008;Zhang et al, 2014), the number of MIS are also significantly increased (Booker et al, 2019). This structural plasticity mechanism could be driven by differences in cortical network activity.…”
Section: Discussionmentioning
confidence: 99%